Iowa birds collected during 1934 - DuMont, Philip A. (Philip Atkinson), 1903-1996 (1934)
Report listing bird specimens collected. This report submitted by Philip DuMont lists the specimens he collected during 1934. These birds, eggs and nests are stored in his home in Des Moines with the exception of some specimens that were forwarded to Myron Swenk at the University of Nebraska for study.